Solving the Terminology Problem of Accounting Manipulations (Earnings Management and Creative Accounting) - Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2022)
The work presents a variety of terms that name accounting manipulations. After analyzing scientific sources and conducting an analysis of the bibliographic data of the publications presented on the Web of Science website, the terminology problems prevailing in foreign and Lithuanian literature are revealed. This terminology brings a lot of confusion when dealing with the problem of accounting manipulations. The article examines the reasons for the use of different terms, presents the results of the conducted expert assessment. Experts appreciated the phenomenon – accounting manipulations that affect the amount of profit. They named associations derived from the terms "earnings management" and "creative accounting" used in Lithuanian literature. According to experts, the Lithuanian term that best reflects the phenomenon is manipulative accounting. The article presents the definition of manipulative accounting, which is constructed on the basis of the literature analysis.
Keywords: accounting manipulations; earnings management; creative accounting; manipulative accounting